2021
DOI: 10.1101/2021.05.12.443923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple brace root phenotypes promote anchorage and limit root lodging in maize

Abstract: A changing global climate brings increasingly prevalent and severe storms that threaten crop production by imparting mechanical stresses. Plant failure due to mechanical stress is termed lodging and in the United States, yield loss due to lodging has been estimated at 7-25% for maize (Zea mays). In maize, the presence of specialized aerial brace roots has been shown to increase anchorage and root lodging resistance. However, beyond scoring for presence, there have been limited attempts to define the brace root… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, Sharma and Carena (2016) reported that there was no correlation between plant height and root lodging during natural root lodging events. Notable, Hostetler et al (2021) described the low positive correlations between brace root phenotypes and plant height, and analyzed their opposing effects on lodging susceptibility. The taller plants are susceptible to lodging, but stronger brace roots provide them with more lodging-resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sharma and Carena (2016) reported that there was no correlation between plant height and root lodging during natural root lodging events. Notable, Hostetler et al (2021) described the low positive correlations between brace root phenotypes and plant height, and analyzed their opposing effects on lodging susceptibility. The taller plants are susceptible to lodging, but stronger brace roots provide them with more lodging-resistance.…”
Section: Discussionmentioning
confidence: 99%